2018
DOI: 10.1364/boe.9.003731
|View full text |Cite
|
Sign up to set email alerts
|

High-speed, ultrahigh-resolution distal scanning OCT endoscopy at 800 nm for in vivo imaging of colon tumorigenesis on murine models

Abstract: We present the first, most compact, ultrahigh-resolution, high-speed, distal scanning optical coherence tomography (OCT) endoscope operating at 800 nm. Achieving high speed imaging while maintaining an ultrahigh axial resolution is one of the most significant challenges with endoscopic OCT at 800 nm. Maintaining an ultrahigh axial resolution requires preservation of the broad spectral bandwidth of the light source throughout the OCT system. To overcome this critical limitation we implemented a distal scanning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…This SD-OCT system incorporated a distal scanning endoscope. 8 The distal-end scanning endoscope employed a 1.9 mm diameter DC micromotor along with a micromirror to perform circumferential beam scanning. The micromotor was capable of rotating up to 300 rotations/second.…”
Section: Methods and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This SD-OCT system incorporated a distal scanning endoscope. 8 The distal-end scanning endoscope employed a 1.9 mm diameter DC micromotor along with a micromirror to perform circumferential beam scanning. The micromotor was capable of rotating up to 300 rotations/second.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Distal scanning endoscopes with miniature micromotors are an alternative for performing circumferential beam scanning that can avoid the aforementioned resistance-based image distortions. [2][3][4][5][6][7][8][9] Due to size constraints, micromotors incorporated in distal scanning endoscopes often lack feedback mechanisms such as encoders, making it difficult to maintain the rotational velocity. Distal scanning catheters can also exhibit NURD due to an imbalanced load on the motor shaft, or simply due to mechanical instabilities at higher speeds.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the reflection mirror can be rotated with a high-speed miniature DC motor to scan the beam in a helical fashion to form an extended FOV. 42,43 The 500-μm working distance of the current design is optimized for mucosa penetration, and the penetration depth in teeth can reach as deep as ∼2 mm. Dynamic focus tuning through a solid tunable lens [44][45][46] or shape memory alloy 47 can also be implemented in future designs to better accommodate different imaging setups.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical translation of PR-OCT requires integration of the probe into the colonoscope for "optical biopsy" in real time during endoscopic evaluation. Several studies have demonstrated the feasibility of endoscopic OCT in both rodent and human models [17][18][19]26,27], especially, cameraguided endoscopic OCT [24,25]. Current screening methods for colorectal tissue rely on histologic evaluation of biopsy specimens, which take days to receive.…”
Section: Discussionmentioning
confidence: 99%
“…In prior work, several research groups have demonstrated promising results that suggest OCT, an established high resolution imaging modality [9][10][11][12][13], may address the shortcomings of traditional camera endoscopy in the upper gastrointestinal tract [14][15][16] or large intestine [17][18][19]. OCT has been shown to accurately differentiate abnormal from normal tissue in multiple organs as an "optical biopsy" tool [20][21][22][23] in both murine and human colorectal models [24][25][26][27]. However, clinical application of the technology is complicated by the large volume of data generated and the subtle qualitative differences between normal and abnormal tissue.…”
Section: Ivyspringmentioning
confidence: 99%